A metabolomic approach to dry eye disorders. The role of oral supplements with antioxidants and omega 3 fatty acids - Galbis-Estrada, Carmen; Pinazo-Durán, Maria Dolores; Martínez-Castillo, Sebastián; Morales, José M; Monleón, Daniel; Zanon-Moreno, Vicente (Molecular vision, 2015)
We used nuclear magnetic resonance spectroscopy of hydrogen-1 nuclei ((1)H NMR S) to analyze the metabolic profile of reflex tears from patients with dry eye disorders. We performed a prospective case-control study involving 90 participants: 55 patients diagnosed with dry eye syndrome (DESG) and 35 healthy subjects (control group, CG). From the DESG, two subgroups were formed: mild DES (n=22) and moderate DES (n=33). Participants were prescribed an oral nutraceutic supplementation containing antioxidants and essential polyunsaturated fatty acids to be taken as three capsules per day for 3 months. Reflex tears (20-30 µl) were collected from the tear meniscus of both eyes of each subject with a microglass pipette. Nuclear magnetic resonance (NMR) spectra were acquired with a standard one-dimensional pulse sequence with water suppression; 256 free induction decays were collected into 64,000 data points with 14 ppm spectral width. Basal tears showed a differential metabolomic profile between groups. Almost 50 metabolites were identified by H cholesterol, N-acetylglucosamine, glutamate, amino-n-butyrate, choline, glucose, and formate were detected before supplementation and choline/acetylcholine after supplementation. The metabolic profile of the tears was statistically different between groups, as well as before and after supplementation. Our data indicate that DES induces changes in the tear metabolic profile that can be modified with appropriate oral supplementation with antioxidants and essential polyunsaturated fatty acids.